Análisis de errores en la interlengua de aprendices de ELE universitarios checos y eslovacos - Rodríguez García, Cristina (Pontes Philologici, 2021)
Title in English: Error Analysis in the Interlanguage of Czech and Slovak University Students of Spanish as a Second Language The monograph studies the written interlanguage in Spanish of a group of Czech and Slovak university students, focusing on analysis of their errors. The main purpose of this study is to find a pattern in these errors and to understand their evolution from the beginning to the end of the three-year bachelor program of Spanish Language and Literature at Masaryk University in Brno (Czech Republic). For this objective we have analyzed a corpus of written texts compiled from 2014 to 2017 and we have classified all the lexical and morhosyntactical errors according to specific criteria, creating a "grammar of errors" on its own. The conclusions indicate that there are no significant differences between errors according to the linguistic groups. This is due to the fact that the majority of these errors show universal learning strategies that do not apply to just one linguistic group. However, the results also show a considerable influence of Czech and Slovak, especially in the lexical errors that occur due to interferences, faux amis and loans. Furthermore, Slovak students have a higher percentage of errors compared to Czech students at the end of their degree, mainly because the essays are longer. This is an outcome of Slovak students taking more risks when they write in Spanish, since they use more language and they choose more complex structures.